From the Development of Catalysts for Alkyne and Alkyne–Nitrile [2+2+2] Cycloaddition Reactions to Their Use in Polymerization Reactions - Okamoto, Sentaro; Sugiyama, Yu-ki (Synlett, 2013)
Several systems consisting of a ligand, a metal compound, and zinc have been developed as catalysts for alkyne cycloaddition reactions and alkyne–nitrile co-cycloaddition reactions. N-Heterocyclic carbene (NHC)–iron(III) chloride–zinc, NHC–cobalt(II) chloride-zinc, and 2-{[(2,6-diisopropylphenyl)imino]methyl}pyridine (dipimp)–iron(III) chloride hexahydrate–zinc systems catalyzed intramolecular cyclotrimerization reactions of alkynes. The dipimp–cobalt(II) chloride hexahydrate–zinc system catalyzed cycloaddition reactions of a variety of alkynes in intramolecular, partially intramolecular, and fully intermolecular fashions. The ethane-1,2-diylbis(diphenylphosphine)–cobalt(II) chloride hexahydrate–zinc system was effective in catalyzing the [2 + 2 + 2] co-cycloaddition of diynes with nitriles. Nickel complexes with an ionic liquid-tagged ligand converted 1,6-diynes into the corresponding cyclooctatetraenes in a toluene–ionic liquid biphasic system in the presence of zinc. The dipimp–nickel(II) chloride hexahydrate–zinc catalyst polymerized 1,6-diynes to form conjugated polyene cyclic polymers. These results and their applications in synthesis, including controlled polymerization reactions, are described.1 Introduction2 Alkyne [2+2+2] Cycloaddition2.1 Development of N-Heterocyclic Carbene–Cobalt or Iron Compound–Zinc Catalyst Systems2.2 Development of 2-{[(2,6-Diisopropylphenyl)imino]methyl}pyridine–Cobalt or Iron Salt–Zinc Catalyst Systems2.2.1 Development of 2-{[(2,6-Diisopropylphenyl)imino]methyl}pyridine–Iron Chloride–Zinc Catalyst Systems2.2.2 Development of the 2-{[(2,6-Diisopropylphenyl)imino]methyl}pyridine–Iron Chloride Hexahydrate–Zinc Catalyst System2.3 The 2-{[(2,6-Diisopropylphenyl)imino]methyl}pyridine–Cobalt(II) Chloride Hexahydrate–Zinc Catalyst System2.3.1 Reactivity and Functional Group Compatibility2.3.2 Catalyst Activation3 Alkyne–Nitrile [2+2+2] Co-cycloaddition4 Applications4.1 Uses in Organic Synthesis4.2 Use as a Method for Polymer Synthesis4.2.1 Preparation of Diverse Polymerizable Molecules (a Monomer Library)4.2.2 Use in Polymer Functionalization4.2.3 Use as a Polymerization Reaction5 Other Reactions5.1 Nickel-Catalyzed [2+2+2+2] Cycloaddition and Cycloaddition Polymerization of 1,6-Diynes5.2 Hydroalkynylation of Internal Alkynes6 Conclusion
Keywords: alkynes; arenes; cobalt; cycloadditions; homogeneous catalysis; iron; nickel; nitriles; polymers; pyridines; transition metals